REGIONAL VARIATION OF MEHG RATIO TO TOTAL HG IN FISHES FROM KOREAN CITIES - PARK, HYUN MEE; Jung Min ji; Lee Seon hwa; Seo Joo ee; PARK, KYUNG SU; Pyo, Heesoo; Hye-Jung Yoon (Institute of Chemical Technology Prague, 2011)
Total mercury and methylmercury in 14 kinds of fishes from six Korean cities in 2010 were determined with DMA(direct mercury analyzer) and GC/ECD. No pretreatment is needed in DMA but for methylmercury with GC/ECD and methods were validated. Correlations of methylmercury(MeHg) with total mercury(Hg) were investigated in tuna, shark, whale, cutlassfish, mackerel and mackerel pike. Ratio of MeHg to total Hg were 0.45, 0.62, 0.16, 0.38, 0.38 for tuna, cutlassfish, shark, whale and mackerel/mackerel pike, respectively. Linearity of correlation was relatively good for tuna and cutlassfish(R2=0.75, 0.51, respectively) which means that ratio of MeHg to total Hg can be the marker for the species of fishes. Ratio of MeHg to total Hg in fishes were almost same from Seoul, Busan, Incheon cities (0.41~0.47). Ratio were high at Gwangju(0.68) and Daegu(0.55) and low at Gangneung(0.36). Concentration of total Hg and MeHg in tuna at Daegu was very high compared to tuna concentration of other cities. Linearity of correlation was very good at Gangneung and Gwangju (R2=0.82) which indicates that ratio of MeHg to total Hg can be the marker for the origin of mercury contamination. Further investigation for more samples and the correlation with the blood sample from cities will be needed.
Keywords: Methylmercury; Mercury; fish; Regional variation